Body size in early life and the risk of postmenopausal breast cancer - Yang, TO; Cairns, BJ; Pirie, K; Green, J; Beral, V; Floud, S; Reeves, GK (BioMed Central, 2022)
Background Greater early life adiposity has been reported to reduce postmenopausal breast cancer risk but it is unclear whether this association varies by tumour characteristics. We aimed to assess associations of early life body size with postmenopausal breast cancer and its subtypes, allowing for body size at other ages.